KAJIAN POTENSI EKOWISATA MANGROVE DI DESA SIALANG BUAH KECAMATAN TELUK MENGKUDU KABUPATEN SERDANG BEDAGAI Study of Ecotourism Potential of Mangrove in Sialang Buah Village Teluk Mengkudu District Serdang Bedagai Regency - Muhammad Rizky; Yunasfi Djayus; Muhammad Riza Kurnia Lubis (AQUACOASTMARINE, 2016)
Indonesia is the largest archipelago in the world which consists over 17,000 islands and has a coastline of 81,000km. The existence of natural resources the driving factors in making tourism. Sialang Buah beach is located at Sialang Buah village in Teluk Mengkudu district. Research on the tourism potential of mangroves at Sialang Buah village needs to be done to develop the area of eco-tourism aspect. The purpose of this research was to determine the potential and condition of the resource that can be performed and assess the appropriateness and the carrying capacity of mangrove ecosystems for the management of mangrove ecotourism. The research was conductedin June-July 2013at SialangBuah villagein Teluk Mengkudu district, SerdangBedagai city. Based on research, the mangrove ecosystem in Sialang Buah village is dominated by five species of mangrove, which Avicennia marina, Bruguiera cylindrica, Rhizophora apiculata, Sonneratia alba, and Xylocarpus granatum. The density value most species of great value is Rhizopora apiculata and Avicennia marina. Results obtained suitability index for tourist activities mangrove ecosystem in Sialang Buah Village included the category corresponding conditional (SB).There are two proposed location tracks, that waters track and the in lands. The value of the region carrying capacity of water track is 80 people per day and a land track is 160 people per day.Keywords: Ecotourism, Mangrove, Sialang Buah